Coming home art & The Great Hunger - O'Sullivan, Niamh 1960-; Geary, Laurence M.; Mac Suibhne, Breandán; Reilly, Ciarán ca. 20./21. Jh (Ireland's Great Hunger Museum, 2018)
"The scale of the Great Irish Famine, and the horror of it, were unprecedented. It permeated everything, the traces of which remain to this day. But the visual dimensions of the loss of life and the erosions of language and culture remained unaddressed until Quinnipiac University opened Ireland's Great Hunger Museum in 2012, to considerable acclaim. As a largely invisible trauma whose consequences were intrinsic to the subsequent development of Ireland - no less than the United States - the museum collects and displays images and supporting documentation that address both the lacunae and interconnections in representations of the Great Hunger in Irish and diasporic history, culture, and memory. Now, mindful of the suffering of so many, a large number of whom nonetheless went on to contribute so much to America, Quinnipiac University brings its collection home, to share with the people of Ireland. Coming Home: Art and the Great Hunger is an important act of cultural reconnection with Ireland's past and living diaspora, and is a major cultural, educational, and tourist event of local, national, and international interest."--Amazon
Exhibition dates & venues: 8 March-30 June 2018: The Coach House, Dublin Castle ; 20 July-13 October 2018: Uillinn: West Cork Arts Centre, Skibbereen ; 18 January-16 March 2019: Cultúrlann Uí Chanáin, Derry
Keywords: Kunst; Hungersnot -- Motiv; Irland; Famine (Ireland : 1845-1852); Art, Irish; Art, Irish / Exhibitions; Ireland / History / Famine, 1845-1852 / Exhibitions; Art / Ireland / Exhibitions; Art; Ireland; 1845-1852; Exhibition catalogs; History; Ausstellungskatalog -- Dublin Castle, The Coach House -- 08.03.2018-30.06.2018 -- Dublin; Ausstellungskatalog -- West Cork Arts Centre -- 20.07.2018-13.10.2018 -- Skibbereen; Ausstellungskatalog -- Cultúrlann Uí Chanáin -- 18.01.2019-16.03.2019 -- Derry